2021
DOI: 10.1071/ch20372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Continuous-Flow Photo-Bromination Using

Abstract: A continuous-flow photo-bromination reaction on benzyl and phenyl groups was conducted using N-bromosuccinimide as the bromine source inside a preparatory-scale glass plate reactor. This flow reactor system was capable of independently controlling light intensity, wavelength, and reaction temperature, hence exerting an exceptional level of control over the reaction. A short optimisation study for the synthesis of 2-bromomethyl-4-trifluoromethoxyphenylboronic acid pinacol ester resulted in best conditions of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…N-Bromosuccinimide (NBS) was also used by researchers at CSIRO Manufacturing for the photobromination of benzyl and phenyl rings in continuous-flow (Scheme 106). 596 First an optimization was carried out in flow for light wavelength, temperature, solvent and NBS loading in a Corning G1 photoreactor. Notably, when reactions were run with 1.5 equiv of NBS, the competitive dibromination of the benzyl ring occurred.…”
Section: Photocleavage and Photodeprotectionmentioning
confidence: 99%
“…N-Bromosuccinimide (NBS) was also used by researchers at CSIRO Manufacturing for the photobromination of benzyl and phenyl rings in continuous-flow (Scheme 106). 596 First an optimization was carried out in flow for light wavelength, temperature, solvent and NBS loading in a Corning G1 photoreactor. Notably, when reactions were run with 1.5 equiv of NBS, the competitive dibromination of the benzyl ring occurred.…”
Section: Photocleavage and Photodeprotectionmentioning
confidence: 99%
“…Without an adequate number of photons being absorbed by the reaction, the bromination chain reaction could not be sustained, and thus the reaction began to stall. The level of dibrominated product ( 3 ) also rapidly decreased, and this is in accordance with previously published reports by Kappe et al and Waterford et al who observed the decrease in dibrominated product when the temperature was reduced. A recent report by Pliego and Lopes supports this computationally as the barrier to the second bromination is energetically unfavorable, however the second bromination takes place 1.3 kcal mol –1 above the first bromination, suggesting both thermal and light energy control are important for selectivity.…”
Section: Results and Discussionmentioning
confidence: 99%